A escrita dialógica: investigando o relacionamento do sujeito com o próprio texto - Santos, Carla Andréia Thadei Nunes [UNESP] (2015)
The aim of this study is to assess the relationship that students in 9th grade of elementary school set to the text that produce the so-called test writing, noting the possible traits that would show the dialectic construction of themselves as discursive subject and the consequent development of the representation the discursive functionality, so dialogue, the first language, in its written modality.Theoretical and methodologically grounded in sociointeractionist contribution of Vygotsky's guidance, and dialogism of Bakhtin, the study finds that, from a dialectical perspective, the subject and the language mutually constitute interlocutives processes. It is known from this that the kind of relationship that the speaker has with the language will determine the model of representation that builds on its functional dimension. Thus, besides the established relationship of nature, it's examine aspects of construction and issues involved in it, as factors that cause it and the degrees of textuality and discourse resulting. It is worth examining to what extent the composition test context appears as interlocutive, dialogic instance, by means of which that dialectic construction (not) occurs. How does this impact as the discursive constitution of the subject? The answer could be reflected even in nature, quality and level of commitment that the speaker apprentice firm with his text, defined such levels, dialogical parameters of writing, considered in interaction author-text-reader